2012
DOI: 10.1063/1.3679171
|View full text |Cite
|
Sign up to set email alerts
|

Product angular distributions in the ultraviolet photodissociation of N2O

Abstract: The angular distribution of products from the ultraviolet photodissociation of nitrous oxide yielding O( 1 D) and N 2 (X 1 + g ) was investigated using classical trajectory calculations. The calculations modeled absorption only to the 2 1 A electronic state but used surface-hopping techniques to model nonadiabatic transitions to the ground electronic state late in the dissociation. Observed values of the anisotropy parameter β, which decrease as the product N 2 rotational quantum number j increases, could be w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…We have studied the photodissociation of N 2 O in a series of papers and essentially all experimental results have been well reproduced. [41][42][43][44][45][46][47][48][49] A consistent and nearly complete picture has thus been obtained. This paper is part of a similar investigation of the UV photodissociation of OCS.…”
Section: Introductionmentioning
confidence: 57%
“…We have studied the photodissociation of N 2 O in a series of papers and essentially all experimental results have been well reproduced. [41][42][43][44][45][46][47][48][49] A consistent and nearly complete picture has thus been obtained. This paper is part of a similar investigation of the UV photodissociation of OCS.…”
Section: Introductionmentioning
confidence: 57%
“…In Ref. 17 it was shown for N 2 O that the coupling term with respect to motion in R is much smaller and the same is assumed for OCS; because of the considerably smaller excess energy and the higher reduced mass the velocityṘ is smaller for OCS dissociation. The CO vibration remains almost unexcited along the trajectory (see below) and therefore the coupling with respect to r also can be neglected.…”
Section: Product State Distributionsmentioning
confidence: 99%
“…This restriction provided a trustworthy description of the photoexcitation of N 2 O. 13,17,28 Subsequent calculations, however, showed that for OCS higher states need to be included in the CASSCF averaging. The reason is probably intensity borrowing from the bright 4 1 A state.…”
Section: A New Transition Dipole Moment Functions For a B And Cmentioning
confidence: 99%
See 2 more Smart Citations